1993
DOI: 10.1093/bja/71.5.651
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 0.125% Bupivacaine With 0.125% Bupivacaine and Clonidine as Extradural Analgesia in the First Stage of Labour

Abstract: We have studied 42 healthy parturients with singleton vertex pregnancies, who were in the first stage of labour and requesting extradural analgesia. They were allocated randomly in a double-blind fashion to receive either 0.125% bupivacaine plain or 0.125% bupivacaine with clonidine 120 micrograms. Efficacy of analgesia was evaluated using linear visual analogue scoring (VAS), sensory block was assessed using bilateral pinprick in the mid-clavicular line and sedation scored on a five-point scale. Maternal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 28 publications
3
26
1
Order By: Relevance
“…When comparing the labor analgesia obtained with bupivacaine added to 75 µg clonidine with that obtained for the control group, other authors have observed better analgesia in the clonidine group. 13,15 The need for additional local anesthetic among the patients in the present study demonstrated that clonidine allowed the duration of analgesia in the RC group to be equal to that of the R group. Cigarini et al 13 demonstrated that patients who received only bupivacaine required additional local anesthetic for labor analgesia within a shorter period of time than did women who received clonidine.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…When comparing the labor analgesia obtained with bupivacaine added to 75 µg clonidine with that obtained for the control group, other authors have observed better analgesia in the clonidine group. 13,15 The need for additional local anesthetic among the patients in the present study demonstrated that clonidine allowed the duration of analgesia in the RC group to be equal to that of the R group. Cigarini et al 13 demonstrated that patients who received only bupivacaine required additional local anesthetic for labor analgesia within a shorter period of time than did women who received clonidine.…”
Section: Discussionmentioning
confidence: 57%
“…The ratio between the fetal and maternal plasma concentration is approximately 0.9, 13,19 since the drug is metabolized less by the fetus and is slowly eliminated by the fetus and neonate. 25 Some studies 13,15 have reported that newborns delivered by mothers who had received clonidine for labor analgesia did not differ from the control group in terms of Apgar score.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Epidural clonidine is likely to induce dose-dependent side effects: & Gin, 1993;Paech et al, 2000;Aveline et al, 2002;Gurses et al, 2003;Roelants et al, 2005); -maternal hypotension (Chassard et al, 1996;Landau et al, 2002;Aveline et al, 2002;Gurses et al, 2003;Roelants et al, 2005;Parker et al, 2007;Wallet et al, 2010); -maternal bradycardia (O'Meara & Gin, 1993;Gurses et al, 2003;Huang et al, 2007); -abnormalities in foetal heart rhythm (Chassard et al, 1996;Tremlett et al, 1999).…”
Section: Outcome Effect Sizementioning
confidence: 99%
“…Epidural clonidine at a dose of 60µg, added to bupivacaine, increased the duration of analgesia in 30%, with no major adverse effects when compared to bupivacaine without additives [2]. Studies with larger epidural clonidine (120-150µg) doses showed significant adverse effects such as sedation, hypotension, bradycardia and fetal heart rate abnormalities [3][4][5][6]. In one study, lower doses (30 µg) showed no significant benefits [7].…”
mentioning
confidence: 99%